Performance of single‐ and double‐effect operable mechanical vapor recompression desalination system adaptable to variable wind energy. (3rd June 2019) - Kim, Yeongmin; Kim, Dong‐kook; Amano, Yoshiharu; Ng, Kim Choon; Chun, Wongee
Summary: This paper deals with the development and operation of a mechanical vapor recompression (MVR) desalination system with improved energy efficiency in harnessing wind energy, which is non‐dispatchable. Its design, construction, and operation details are presented in this paper. Especially, the main focus of developing the system was on the operation of the system in conjunction with variable loads of new and renewable power sources, in particular, varying wind power. That is, the present work has been carried out to assess the feasibility of its operation in light of capacity modulation to match the power generated under various wind speeds. Optimal operation modes of the system were studied, in which single‐ and double‐effect operations were analyzed for their improvement in energy efficiency. The compression ratio of the proposed MVR system was 1.55 at an inverter speed of 55 Hz, which agreed well with its design value. Operation of the main heat exchanger remained stable within the limits of its operable range, although the temperature differences in the main heat exchanger did not remain constant because of the pressure variations in the evaporator. The daily freshwater yield was between 28 and 51 tons. The power consumption per ton of freshwater produced was about 43 kW for a single effect and about 23 kW for a double effect, which is about twice as efficient. Abstract : This paper deals with the design, construction, and operation details of a mechanical vapor recompression (MVR) desalination system with improved energy efficiency in variable wind energy conditions. The results indicated that the power consumption per ton of freshwater production for the single effect mode of operation was about twice more than that for the double‐effect one. Low‐load operation was attainable by controlling the loads of the system by regulating the inverter speed with an electic steam boiler for make‐up steam.